Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Indeks Pembangunan Manusia - Rahmayati, Anim; Pertiwi, Imanda Firmantyas (IAIN Surakarta, 2018)
This study aims to examine the effects of local revenue and balancing funds consisting of general allocation funds, special allocation funds and revenue-sharing funds on the human development index of district governments/ city in Central Java. The level of Human Development Index in Central Java from year to year has fluctuated changes in the increase and including the medium category.The research method used in this is quantitative research using multiple linear regression analysis tools. The sample used in this study is the district government financial statements in Central Java during 2015-2016 which amounted to 70. The result of the research shows that the original income of the region influences the human development index. While general allocation funds, special allocation funds and profit-sharing funds have no effect on the human development index. This indicates that the fulfillment of education, health and poverty eradication needs in Central Java can be met from the local revenue in each district government. Keywords: Local original revenue, general allocation fund, special allocation fund, profit-sharing fund, human development index JEL Classification: H61, H77